2022
DOI: 10.3390/antibiotics11030412
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity Enhancers: Towards Smart Delivery of Antimicrobial Agents

Abstract: The development of effective treatments against infectious diseases is an extensive and ongoing process due to the rapid adaptation of bacteria to antibiotic-based therapies. However, appropriately designed activity enhancers, including antibiotic delivery systems, can increase the effectiveness of current antibiotics, overcoming antimicrobial resistance and decreasing the chance of contributing to further bacterial resistance. The activity/delivery enhancers improve drug absorption, allow targeted antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 219 publications
0
16
0
Order By: Relevance
“…However, to ensure the efficient delivery of all components to the target site, "smart" drug delivery systems may be employed, where the antimicrobial agents could be encapsulated and released at the infection site in response to a stimuli/trigger. 56 This could be an attractive avenue to increase the feasibility of this trisystem strategy for clinical applications. It is envisaged that the tri-system will most likely be more suitable for topical (local) or intravenous than oral administration routes in humans because of the potential degradation of antimicrobial agents in the gastrointestinal tract.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to ensure the efficient delivery of all components to the target site, "smart" drug delivery systems may be employed, where the antimicrobial agents could be encapsulated and released at the infection site in response to a stimuli/trigger. 56 This could be an attractive avenue to increase the feasibility of this trisystem strategy for clinical applications. It is envisaged that the tri-system will most likely be more suitable for topical (local) or intravenous than oral administration routes in humans because of the potential degradation of antimicrobial agents in the gastrointestinal tract.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While there may be concerns regarding the feasibility of having all 3 components at the infection site in vivo, recent studies on binary combination systems involving antimicrobial polymers have shown the successful translation of in vitro antimicrobial efficacies to in vivo animal models (via intraperitoneal and tail vein injections in mouse). , This offers hope that the tri-systems demonstrated here may achieve similar potency in vivo as the in vitro results. However, to ensure the efficient delivery of all components to the target site, “smart” drug delivery systems may be employed, where the antimicrobial agents could be encapsulated and released at the infection site in response to a stimuli/trigger . This could be an attractive avenue to increase the feasibility of this tri-system strategy for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, curcuminoids, particularly CUR, have been complexed with various metals to achieve the desired synergistic effects. These formulations include curcumin–tannic acid-metal complexes (CUR-TA-Fe II and CUR-TA-Fe III) [ 101 ], curcumin–zinc oxide nanoparticles [ 102 ], and gallium–curcumin nanoparticles [ 103 ]. CUR has been reported to possess varying degrees of activity against the following viruses: high-risk human papillomaviruses, coxsackievirus, hepatitis C, herpes simplex virus type 1, influenza viruses (PR8, H1N1, and H6N1), and transmissible gastroenteritis virus [ 100 ].…”
Section: Notable Bioactivitiesmentioning
confidence: 99%
“…In this review, we report and discuss the latest strategies presented in the literature to circumvent Gram-negative bacterial resistance. This review will not deal with immunoconjugates or aptamer strategies, since numerous reviews have been devoted to this strategy [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%